Determinants of individual sustainable investment behavior - A framed field experiment - Gunnar Gutsche; Heike Wetzel; Andreas Ziegler (Philipps-University Marburg, School of Business and Economics, 2020)
This paper employs a new empirical approach for eliciting preferences for and determinants of sustainable investments at the individual investor level. We examine data from an incentivized framed field experiment that was part of a representative survey among financial decision makers in German households. The analysis reveals strong preferences for sustainable funds. These preferences are especially driven by non-pecuniary factors such as financial literacy, environmental values, and social norms. Interestingly, economic preferences or the Big Five personality traits are only of minor relevance. Our results provide useful implications for the discussion on how to mobilize individual investors for sustainable development.
Keywords: G11; Q56; G02; A12; A13; 330; Sustainable investments; individual investors; determinants; revealed preferences; framed field experiment